Still just Grace - Harper, Charise Mericle (Houghton Mifflin Company, 2007)
When a struggling student teacher assigns a group project, seven-year-old Just Grace gets so involved in working with Grace W. and Grace F. that she fails to understand why she and her best friend, Mimi, are drifting apart.